Antibody-modified liposomes for tumor-targeting delivery of timosaponin AIII - Lu, Lu (Int J Nanomedicine, 2018)
INTRODUCTION: Timosaponin AIII (TAIII), as a steroid saponin in Anemarrhena asphodeloides, has favorable potential as an antitumor candidate. However, its hydrophobicity and low bioavailability severely limit its in vivo antitumor efficacy. METHODS: To overcome this drawback, TAIII-loaded liposomes (LP) were prepared to improve TAIII solubility and extend its circulation time. Furthermore, anti-CD44 antibody-modified LP (CD44-LP) was prepared to enhance the therapeutic index of TAIII. The LP and CD44-LP were also characterized through their biological activity, target selective binding and uptake, and in vivo pharmacokinetics. RESULTS: Compared with free TAIII, both LP and CD44-LP possessed a desirable sustained-release profile in vitro, with ~14.2- and 10.7-fold longer TAIII half-life, respectively, and 1.7- and 1.9-fold larger area under the curve, respectively. LP and CD44-LP enhanced TAIII antitumor activity against HepG2 cells and in a xenograft mouse model without detectable toxicity. In particular, CD44-LP exhibited notably higher cytotoxicity than did LP, with a lower half-maximal inhibitory concentration (48 h). CD44-LP exhibited stronger tumor inhibition, and the tumor inhibitory effect was 1.3-fold that of LP. Furthermore, confocal laser scanning microscopy and in vivo near-infrared imaging of a xenograft mouse model revealed that compared with LP, CD44-LP could effectively enhance tumor accumulation. CONCLUSION: Taken together, the results indicate that both CD44-LP and LP can considerably extend TAIII circulation time, increase tumor-targeted accumulation, and enhance antitumor activity. Thus, the anti-CD44 antibody-modified liposome is a promising candidate for treating CD44-positive cancer with considerable antitumor effects.